2015
DOI: 10.1186/s12866-015-0545-y
|View full text |Cite
|
Sign up to set email alerts
|

Serological diagnosis of pulmonary Mycobacterium tuberculosis infection by LIPS using a multiple antigen mixture

Abstract: BackgroundThere is an urgent need for a simple and accurate test for the diagnosis of human Mycobacterium tuberculosis, the infectious agent causing tuberculosis (TB). Here we describe a serological test based on light emitting recombinant proteins for the diagnosis of pulmonary Mycobacterium tuberculosis infection.MethodsLuciferase Immunoprecipitation Systems (LIPS), a fluid-phase immunoassay, was used to examine antibody responses against a panel of 24 different M. tuberculosis proteins. Three different stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…In contrast, our results are largely in agreement with prior studies that have evaluated multiplex serologic testing[ 10 , 25 , 26 ]. Antibody responses in a Brazilian cohort using a panel of 7 antigens (including Rv0934 which also had high variable importance in our study) demonstrated high sensitivity (93%) and specificity (87%) in detecting active TB when compared to TB negative controls from a non-endemic environment[ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, our results are largely in agreement with prior studies that have evaluated multiplex serologic testing[ 10 , 25 , 26 ]. Antibody responses in a Brazilian cohort using a panel of 7 antigens (including Rv0934 which also had high variable importance in our study) demonstrated high sensitivity (93%) and specificity (87%) in detecting active TB when compared to TB negative controls from a non-endemic environment[ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with other studies, we observed a high level of heterogeneity in Ab responses to Mtb proteins, including those with biomarker value (6,7,9,10,31). Hence, our data are consistent with the notion that a single biomarker will not be sufficient for distinguishing TB status in various patient groups (6,32).…”
Section: M-hd-nappa -Conceptsupporting
confidence: 81%
“…The cellular location for two of the proteins (Rv3405c and Rv3544c) has not been identi- fied. All of the four CFPs (Rv0054 (9, 10, 41), Rv0831c (9, 42), Rv2031c (9,10,43,44) and Rv0222 (45,46)), have already been reported in TB serology studies. Rv2031c (hspX) was also previously identified using a Mtb proteomic level microarray with printing of unpurified Mtb proteins generated in E. coli lysate (6).…”
Section: M-hd-nappa -Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…a High nonspecific binding was found with the following fusion proteins (which were excluded from the data analyses): Acr1-MPT83 (Rv2031-Rv2873), DID64 (Rv2031-Rv0934-Rv387), DID82 (Rv1980c-Rv3619-Rv38814), DID88 (Rv2873-Rv1980c-Rv3881), DID90 (Rv2873-Rv0934-Rv2032), and DID99 (Rv1980c-Rv2108-Rv3881 Advances in genomic and proteomic research have made it possible to provide a large-scale characterization of TB biomarkers eliciting antibody responses in humans and nonhuman primates (21)(22)(23). The studies defined the M. tuberculosis immunoproteome to be approximately 10% of the bacterial proteome enriched for membraneassociated and extracellular proteins, which can lead to the development of more accurate serodiagnostic tools (24). Interestingly, the set of 13 serological targets found to be predominantly associated with active TB in humans (22) included only 2 proteins, Rv1980c and Rv2873, identified in the present study among the top 12 antigens recognized by antibodies in M. bovis-infected cattle.…”
Section: Discussionmentioning
confidence: 99%